Practice and knowledge about diagnosis and treatment of alpha-1 antitrypsin deficiency in Spain and Portugal - Esquinas, Cristina; Barrecheguren, Miriam; Sucena, Maria; Rodriguez, Esther; Fernandez, Sandra; Miravitlles, Marc (BMC pulmonary medicine, 2016)
Background Determining physicians’ awareness about alpha-1 antitrypsin (AAT) deficiency (AATD) may help to explain the discrepancy between the observed and expected number of patients diagnosed with this disease. This study was designed to assess the opinions on knowledge, practice pattern and attitude regarding AATD among physicians in Spain and Portugal. Methods An online anonymous survey was performed on pulmonologists ( n = 100), internal medicine specialists (IMS) ( n = 100) and primary care physicians (PCP) ( n = 176). Of the total number of physicians, 221 were from Spain, and 155 were from Portugal. Physicians answered 21 questions related to their personal and professional profile, knowledge regarding AATD and chronic obstructive pulmonary disease (COPD), performance and attitude about AATD, and use of augmentation therapy. Responses were ranked on a 4-point scale indicating the level of agreement. In addition, some of the responses were rated as either “low” or “high” indicating the level of knowledge the respondent felt he/she possessed. Results Only 14 % of physicians reported to “know very well” about AATD (3.3 [SD 0.6] for pulmonologists vs. 2.64 [SD 0.60] for IMS and 2.48 [SD 0.71] for PCP; p < 0.001). Only 45.2 % of physicians correctly answered “<50 mg/dL” as the threshold value of serum AAT to be considered severe AATD (55.0 % of pulmonologists vs. 47.0 % of IMS and 38.6 % of PCP; p = 0.001). Choice of the correct answer did not agree with those physicians self-declaring a high level of AATD knowledge (51.2 %). A total of 43.9 % of physicians correctly identified all diseases or conditions in a list associated or not with AATD. A similar trend was detected when identifying which conditions would be responsive to augmentation therapy (<50 %). Only 15.8 % of specialists performed AATD testing in all patients with COPD (27.0 % pulmonologists, 12.6 % PCP; p = 0.001). Conclusion The results suggest that a knowledge gap may be contributing to the underdiagnosis of AATD. Physicians in Spain and Portugal showed a marked lack of awareness of their shortcomings in knowledge about AATD, and in general did not follow guidelines and recommendations for AATD testing.